(3QSGdI aj GdYed HGdGSWQdGH GdSQWGfjs - (3GdeNRhej GdNGdOj, CHh YHO Gddg, GHf GdbjSQGfj, TQa GdOjf, eMeO Hf fUQ Hf UZjQ Hf OGZQ (B, 548 (3g`s
(3ChdgG (B:s
(3HSe Gddg GdHGH GdChd aj GhVGY GdGSWQdGH bO bGe GdHQgGf GdgfOSj aj cJH Yed gPg GdBdI Cfg G jecf Cf jhLO GSWQdGH jDOj Edi GdMW ef CYeGd GdMSGH GdJYdjejI Ydi ZjQ GdhVYjf GdeYQhajfs
(3BNQgG (B:s
(3GdHGH GdKGdK hGdYTQhf aUd hbO JhLO GdSGYGJ aj GdfUa GdCSad ef GdUMjaI ef hVYjf CjVG TeGdj hLfhHj aEPG cGfJ GdTeS Ydi ebfWQGJ hVY eG hbY fXQgG ef GdSGYGJ Jes
(3Vef eLehY NRGFfjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7\125s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3Gdadc hGdJfLje hGdejbGJs